Prevalence of radiographic asbestosis in crocidolite miners and millers at Wittenoom, Western Australia. - Cookson,WO; De,Klerk NH; Musk,AW; Armstrong,BK; Glancy,JJ; Hobbs,MS (Br J Ind Med, 1986)
An estimate has been made of the prevalence of unrecognised pneumoconiosis in former crocidolite workers from Wittenoom, Western Australia. All plain chest radiographs relating to a one in six random sample (1025 men) of all former Wittenoom workers who had never entered a compensation claim to the Pneumoconiosis Medical Board of Western Australia were sought from Perth teaching hospitals and from the Perth Chest Clinic where compulsory examination of all workers in the mining industry takes place. Radiographs were recovered for 83% of the men and read independently by two observers. By means of logistic regression analysis a current prevalence of parenchymal abnormality (defined as a radiographic profusion of small opacities of category 1/0 or greater on the ILO classification) of nearly 20% was calculated after adjustment for age, time since first exposure, and cumulative exposure level. One hundred men randomly selected from those known to be alive in the sample were invited to attend for a new radiographic examination. Seventy four men attended and the predicted prevalence was confirmed. It is estimated from these data that there were between 450 and 900 former Wittenoom workers in Australia at the end of 1980 who had radiographic abnormality consistent with pneumoconiosis but had not claimed compensation or had asbestosis diagnosed. The data are consistent with there being no threshold dose of crocidolite exposure for the development of radiographic abnormality in this group.